Over-Expressed Pathogenic miRNAs in Alzheimer’s Disease (AD) and Prion Disease (PrD) Drive Deficits in TREM2-Mediated Aβ42 Peptide Clearance - Zhao, Yuhai; Jaber, Vivian; Lukiw, Walter J. (Frontiers in Aging Neuroscience, 2016)
One prominent and distinguishing feature of progressive, age-related neurological diseases such as Alzheimer’s disease (AD) and prion disease (PrD) is the gradual accumulation of amyloids into dense, insoluble end-stage protein aggregates. These polymorphic proteolipid lesions are known to contribute to immunogenic and inflammatory pathology in these insidious and fatal disorders of the human central nervous system (CNS). For example, the evolution of self-aggregating amyloid-beta (Aβ) peptides, such as the 42 amino acid Aβ42 peptide monomer into higher order aggregates are largely due to: (1) the inability of natural processes to clear them from the cellular environment; and/or (2) the overproduction of these amyloid monomers which rapidly mature into higher order oligomers, fibrils and insoluble, end-stage senile plaques. Cells of the CNS such as microglial (MG) cells have evolved essential homeostatic mechanisms to clear Aβ peptides to avoid their accumulation, however when defective, these clearance mechanisms become overwhelmed and excessive deposition and aggregation of these amyloids result. This ‘Perspectives’ paper will highlight some emerging concepts on the up-regulation of an inducible microRNA-34a in AD and PrD that drives the down-regulation of the amyloid sensing- and clearance receptor protein TREM2 (the triggering receptor expressed in myeloid/microglial cells). The impairment of this inducible, miRNA-34a-regulated TREM2- and MG-cell based amyloid clearance mechanism may thereby contribute to the age-related amyloidogenesis associated with both AD and PrD.